2000
DOI: 10.1093/rheumatology/39.1.85
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of vertebral fractures in mild ankylosing spondylitis and their relationship to bone mineral density

Abstract: Spinal and hip osteopenia and vertebral fractures are a feature of mild AS. However, there was no correlation between BMD and vertebral fractures in these patients. AS patients with mild disease had a higher risk of fractures compared with the normal population and this increased with the duration of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
3
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(114 citation statements)
references
References 20 publications
5
96
3
10
Order By: Relevance
“…Different epidemiologic studies report an increase in the risk of developing osteoporosis in various inflammatory conditions [5][6][7][8].…”
Section: Is Osteoporosis An Inflammatory Process?mentioning
confidence: 99%
“…Different epidemiologic studies report an increase in the risk of developing osteoporosis in various inflammatory conditions [5][6][7][8].…”
Section: Is Osteoporosis An Inflammatory Process?mentioning
confidence: 99%
“…There is a close relationship between the immune and skeletal systems [2] and epidemiological studies have demonstrated an increased risk of developing osteoporosis in inflammatory conditions such as ankylosing spondylitis [3], rheumatoid arthritis [4] and inflammatory bowel disease [5]. In addition, pro--inflammatory cytokines have been associated with osteoblast and osteoclast regulation, and with bone resorption [6].…”
Section: Introductionmentioning
confidence: 99%
“…The chronic inflammation causes progressive ossification of the spinal ligaments and facet joints, which eventually results in a fixed and rigid spine [7,8,15]. In addition, AS is also associated with vertebral osteoporosis [18]. Therefore, AS patients in advanced stage are more susceptible to fracture due to the rigidity of the ossified spine and osteoporosis [18,19,22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, AS is also associated with vertebral osteoporosis [18]. Therefore, AS patients in advanced stage are more susceptible to fracture due to the rigidity of the ossified spine and osteoporosis [18,19,22]. A stress fracture is most likely to occur in thoracolumbar junction, a region with tremendous stress forces concentrated [4].…”
Section: Introductionmentioning
confidence: 99%